2021
DOI: 10.3390/pharmaceutics13122053
|View full text |Cite
|
Sign up to set email alerts
|

New Applications of Lipid and Polymer-Based Nanoparticles for Nucleic Acids Delivery

Abstract: Nucleic acids represent a promising lead for engineering the immune system. However, naked DNA, mRNA, siRNA, and other nucleic acids are prone to enzymatic degradation and face challenges crossing the cell membrane. Therefore, increasing research has been recently focused on developing novel delivery systems that are able to overcome these drawbacks. Particular attention has been drawn to designing lipid and polymer-based nanoparticles that protect nucleic acids and ensure their targeted delivery, controlled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…However, it needs to be mentioned that the manufacturer’s structures for Lipofectamine do recommend removing serum from the media while exposing the cells to this transfection agent. Rapid enzymatic degradation is one of the major challenges in efficient nucleic acid delivery . This vulnerability is one of the drawbacks of the siRNA conjugates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it needs to be mentioned that the manufacturer’s structures for Lipofectamine do recommend removing serum from the media while exposing the cells to this transfection agent. Rapid enzymatic degradation is one of the major challenges in efficient nucleic acid delivery . This vulnerability is one of the drawbacks of the siRNA conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Rapid enzymatic degradation is one of the major challenges in efficient nucleic acid delivery. 46 This vulnerability is one of the drawbacks of the siRNA conjugates. For example, it has been shown that phosphothioethanol conjugated siRNA can only extend the degradation time from 0.5 to 6 h. 47 A higher level of protection is usually expected from "encapsulation" approaches that limit the access to siRNA and have been reported to protect siRNA for up to 24 h in the presence of serum.…”
Section: Serum Stability Of the Peptide/sirna Complexmentioning
confidence: 99%
“…Despite being recognized for a long time, endosomal escape remains one of the unresolved bottlenecks in the way of effective LNP design [136]. Following the cellular entry, LNPs will be trapped in endosomes, from which only a small fraction may be able to successfully escape.…”
Section: Endosomal Escapementioning
confidence: 99%
“…To overcome these limitations, different nonviral delivery systems, such as cationic polymers, lipids, inorganic nanoparticles, and dendrimers, have been developed. These formulations showed varying levels of success in delivering nucleic acids into cells. ,, An alternative approach of polymer–lipid hybrid nanoparticles has been investigated for nucleic acid delivery due to their attractive properties of biocompatibility, biodegradability, and ease of synthesis. Previous studies showed that polymer–lipid nanoparticles efficiently deliver drugs, mRNA, plasmid DNA, and siRNA into cells. Hybrid nanoparticles protect nucleic acids from degradation by nucleases. , They can interact with the cell membrane and internalize into cells by endocytosis. Recent studies showed that polymer–lipid nanoparticles promote nucleic acid escape from the endolysosomal compartments and increase gene silencing efficiency. Then, the conjugated nucleic acids are released from the carrier system in the cytosol, where RNAi is initiated .…”
Section: Introductionmentioning
confidence: 99%